Esophagoplasty Using a Jejunum Segment on a Vascular Pedicle - D. V. Ruchkin; V. A. Kozlov; M. M. Khamidov; D. E. Okonskaya; N. B. Kovalerova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to substantiate the expediency of using a segment of the jejunum on a vascular pedicle in esophagoplasty.   Materials and methods. At the National Medical Research Center of Surgery named after A.V. Vishnevsky, 12 patients underwent esophagoplasty with a combined visceral transplant, of which 9 (75.0 %) received a gastrointestinal graft and 3 (25.0 %) — a colon-jejunum one. Esophagectomy with simultaneous esophageal plastic surgery was performed in 10 (83.3 %) patients, in 4 (40 %) of them — in combination with distal gastric resection. The indication for surgery in 3 patients was cicatricial stricture of the esophagus and stenosis of the pylorus, in 2 — achalasia of the cardia of the terminal stage (in one patient — with ulcerative stenosis of the pylorus). Three more patients underwent esophagectomy due to peptic strictures: esophagogastroanastomosis (n = 1), esophagoenteroanastomosis (n = 1) and esophagus after Nissen surgery (n = 1). Cancer recurrence after proximal gastric resection and gastrectomy in 2 patients was an indication for esophagectomy. Also, 2 (16.7 %) patients were hospitalized in the National Medical Research Center of Surgery named after A.V. Vishnevsky with incomplete esophagoplasty: one person — after Dobromyslov — Torek surgery for spontaneous rupture of the esophagus, and one patient — after the unsuccessful Lewis surgery for esophageal cancer performed in other hospitals.   Results. The average duration of post-operative stay was 12.7 ± 6.3 days. The postoperative period was smooth in 10 (83.3 %) patients. The failure of the cervical anastomosis was revealed in 1 (8.3 %) patient on day 5 after esophageal plastic surgery with colon-jejunum graft, which was resolved conservatively without repeated surgery. Relaparotomy was required in one patient on day 7 after surgery for bile peritonitis, the cause of which was destructive acalculous cholecystitis with perforation. All 12 patients were discharged from the clinic with full nutrition through the mouth. In the long-term period, 11 (91.7 %) patients remained under observation, 1 (9.1 %) developed an esophagogastroanastomosis stricture 1.5 months after esophageal plastic surgery, which was resolved by 4 courses of bougation during the first 9 months after surgery. No other complications were noted.   Conclusion. The segment of the jejunum on the vascular pedicle, used for esophagoplasty, in the condition of a shortage of plastic material, allows not only to complete the reconstruction at once, but also to restore the natural passage of food and prevent bile reflux.